2016
DOI: 10.3389/fpubh.2016.00266
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Care for Falls via Emergency Responders: A Feasibility Study of a Brief At-Scene Intervention

Abstract: Falls account for a substantial portion of 9-1-1 calls, but few studies have examined the potential for an emergency medical system role in fall prevention. We tested the feasibility and effectiveness of an emergency medical technician (EMT)-delivered, at-scene intervention to link elders calling 9-1-1 for a fall with a multifactorial fall prevention program in their community. The intervention was conducted in a single fire department in King County, Washington and consisted of a brief public health message a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…In a recent intervention study leveraging an EMS‐delivered on‐scene intervention for individuals who called 911 for a fall, the perception of the EMS providers was that the intervention was feasible and led to resultant referrals to a multifactorial fall prevention program . The strategy for linking people with fall prevention opportunities included a brief public health message about preventability of falls and a fall prevention program pamphlet given to individuals at the scene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent intervention study leveraging an EMS‐delivered on‐scene intervention for individuals who called 911 for a fall, the perception of the EMS providers was that the intervention was feasible and led to resultant referrals to a multifactorial fall prevention program . The strategy for linking people with fall prevention opportunities included a brief public health message about preventability of falls and a fall prevention program pamphlet given to individuals at the scene.…”
Section: Discussionmentioning
confidence: 99%
“…Although the information left at the scene statistically increased enrollment of people in a fall prevention program, fewer than 35% of individuals given the information reported that they had EMS discuss falls with them at the time of 911 call, and only 3% more individuals given the information than in the control group enrolled in fall‐prevention programs. Although only a few individuals enrolled in a fall‐prevention program after EMS education after a fall, this strategy was cost effective, was supported by EMS providers, and has the potential to create a new pathway for activating fall prevention strategies and education . These concepts build on the SAFER trials performed in the United Kingdom that concluded that involving EMS in fall reduction strategies is feasible and effective, but further work on timing of the intervention, whether to activate fall prevention strategies and education at the scene or at a later date, may prove to be more effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This intervention strategy holds great potential because EMS first responders are trusted members of the community with the ability to educate and influence health behavior ( 30 ). While some evidence-based fall prevention interventions delivered by emergency personnel exist (e.g., Remembering When) ( 31 ), other opportunities exist for EMS to adopt fall prevention efforts in their routine practice ( 32 ). Such interventions hold great potential to prevent falls because EMS first responders can educate older adults about fall-related risk, perform environmental scans to correct modifiable home safety issues, and make referrals to other fall prevention resources in the community.…”
Section: Discussionmentioning
confidence: 99%